Washington View: Moving ahead after November elections. (November 2014) - Ferguson, Maria
The outcome of the November elections in Washington for House and Senate seats, along with the 36 governor offices up for votes means that there may be a very different political landscape come January. But perhaps the greatest promise of the results of the upcoming elections is that Congress and state houses could find some common ground and new leaders may emerge to move the nation toward addressing sorely neglected education issues.